Systellaspis pellucida Filhol 1884 - Alves-Júnior, Flavio De Almeida; Silva, Elinai Dos Santos; Araújo, Marina De Sá Leitão Câmara De; Cardoso, Irene; Bertrand, Arnaud; Souza-Filho, Jesser F. (Zenodo, 2019)
Systellaspis pellucida (Filhol, 1884) (Fig. 37 A–C, 38) Acanthephyra pellucida Filhol, 1884: 144, 162.— Perrier 1886: 330.— Kemp 1910: 66. Acanthephyra affinis Faxon, 1896: 162, pl. 2, figs 1–3.— Kemp 1906: 21. Systellaspis affinis de Man, 1920: 43.— Chace 1936: 29.— Calman 1939: 190.— Springer & Bullis 1956: 11.— Forest 1964: 621.— Bullis & Thompson 1965: 7. — Monod 1966: 110.— Crosnier & Forest 1968: 1133. Systellaspis pellucida— Crosnier & Forest 1973: 92, figs 26c, 27c;— Chace 1986: 67, figs 34m–o, 35g, h.—Crosnier 1987: 720.— Poupin 1996: 6.— Cardoso & Young 2005: 70, figs. 54–58.— Pequegnat & Wicksten 2006: 102.— Poupin 2010: 73. Material examinad . 1 F, Rocas Atoll, Abracos 1 ST# 04/ Leg. 1, Midwater tow, 85 m, 04° 05,37’ S / 032° 10,86’ W, 0 2 October 2015, MOUFPE: 15.538. Diagnosis : Carapace with rostrum overreaching scaphocerite, dorsal margin with 9–11 teeth and 5–6 pre-orbital spines, ventral margin with 3–6 teeth; strong antennal spine present; branchiostegal spine present with distinct carina. Abdomen not dorsally carinate on all somites; somites 3–5 with posteromesial tooth, the one of somite 3 distinctly strong (modified by Cardoso & Young 2005). Distribution : Western Atlantic: Gulf of Mexico, Bahamas, Antilles, Brazil ( Rocas Atoll and Bahia). Eastern Atlantic: West African coast, from Cape Verde, Guinea, Gabon. Indo-Pacific Oceans: Madagascar, Western Indian Ocean, South China Sea, Zanzibar, Philippines, Indonesia, New Caledonia, Tuamotu Island, Hao Island (Crosnier & Forest 1973; Chace 1986; Cardoso & Young 2005; Pequegnat & Wicksten 2006) (Fig. 38). Bathymetric distribution : 300–3700 m depth (Crosnier & Forest, 1973; Chace, 1986; Crosnier 1987; Cardoso & Young 2005), herein this specimen was found in Rocas Atoll at a depth of 85 m, thus extending its bathymetric distribution from shallow waters. Remarks : The specimens analyzed herein are in accordance with the descriptions provided by Crosnier & Forest (1973), Chace (1986) and Cardoso & Young (2005). Systellaspis pellucida occurs in the Indian, Pacific and Atlantic Oceans (Fig. 38) in mesopelagic zones as observed by Cardoso & Young (2005). The first record in Brazilian waters was made by Cardoso & Young (2005) from state of Bahia. In the material sampled in Rocas Atoll, the species was collected in micronekton net shallow waters (85 m). Thus, this paper brings the second record of this species from the Brazilian waters and the first observation in an oceanic island (Rocas Atoll) located in Southwestern Atlantic. : Published as part of Alves-Júnior, Flavio De Almeida, Silva, Elinai Dos Santos, Araújo, Marina De Sá Leitão Câmara De, Cardoso, Irene, Bertrand, Arnaud & Souza-Filho, Jesser F., 2019, Taxonomy of deep-sea shrimps of the Superfamily Oplophoroidea Dana 1852 (Decapoda: Caridea) from Southwestern Atlantic, pp. 401-442 in Zootaxa 4613 (3) on pages 432-434, DOI: 10.11646/zootaxa.4613.3.1, http://zenodo.org/record/3239769 : {"references": ["Filhol, H. (1884) Explorations sous-marines. Voyage du \" Talisman \". La Nature, 12, 119 - 394.", "Perrier, E. (1886) Les explorations sous-marines. Hachette, Paris, 352 pp.", "Kemp, S. (1910) The Decapoda Natantia of the coasts of Ireland. Reports of the Department of Agriculture and Technical Instruction for Ireland, Scientific Investigations of the Fisheries Branch, 1, 1 - 190. https: // doi. org / 10.5962 / bhl. title. 53732", "Faxon, W. (1896) Reports on the results of dredging, under the supervision of Alexander Agassiz, in the Gulf of Mexico and the Caribbean Sea, and on the East Coast of the United States, 1877 to 1880, by the U. S. Coast Survey Steamer \" Blake \", Lieut. - Commander C. D. Sigsbee, U. S. N., and Commander J. R. Bartlett, U. S. N., commanding. XXXVII. Supplementary notes on the Crustacea. Bulletin of the Museum of Comparative Zoology at Harvard College, 30, 153 - 166.", "Kemp, S. W. (1906) On the occurrence of the genus Acanthephyra in deep water off the West coast of Ireland. Scientific Investigations Fisheries Branch Ireland, 1, 1 - 28.", "de Man, J. G. (1920) Families Pasiphaeidae, Stylodactylidae, Hoplophoridae, Nematocarcinidae, Thalassocaridae, Pandalidae, Psalidopodidae, Gnathophyllidae, Processidae, Glyphocrangonidae and Crangonidae. The Decapoda of the Siboga Expedition. Part IV. Siboga Expedition Leiden, 39 (3), 1 - 318.", "Chace, F. A. (1936) Revision of the bathypelagic prawns of the family Acanthephyridae, with notes on a new family, Gomphonotidae. Journal of the Washington Academy of Sciences, 26, 24 - 31.", "Calman, W. T. (1939) Crustacea: Caridea. Scientific Reports of John Murray Expedition, 6, 183 - 224.", "Springer, S. & Bullis, H. R. (1956) Collections by the Oregon in the Gulf of Mexico. U. S Fish and Wildlife Service Bureau of Commercial Fisheries. Service specially scientific Fisher, 196, 1 - 134.", "Forest, J. (1964) Sur une crevette recueillie au cours de la campagne de chalutage dans le golfe de Guinee Plesionika williamsi sp. nov. Bulletin of Museum of Natural History, Paris, 35 (6), 620 - 629.", "Bullis, H. R. & Thompson, J. R. (1965) Collection by the exploratory fishing vessels Oregon, Silver Bay, Combat, and Pelican made during 1956 - 1960 in the southwestern North Atlantic. United States Fish and Wildlife Service, Special Scientific Report-Fisheries, 510, 1 - 130.", "Monod, T. H. (1966) Crevettes et crabes de la cote occidentale d'Afrique. Memoire de l'Institut Fondamental d'Afrique Noire, Zanzibar, No. 77, 103 - 234, pls. 1 - 26.", "Crosnier, A. & Forest, J. (1968) Note preliminaire sur les carides recueillis par l'Ombango au large du plateau continental, du Gabon a l'Angola (Crustacea Decapoda Natantia). Bulletin du Museum national d'histoire naturelle, Paris, Series 2, 39, 1123 - 1147.", "Crosnier, A. & Forest, J. (1973) Les crevettes profondes de l'Atlantique oriental tropical. Faune Tropicale, 19, 1 - 409.", "Chace, F. A. (1986) The Caridean shrimps (Crustacea: Decapoda) of the Albatross Philippine Expedition, 1907 - 1910, part 4: families Oplophoridae and Nematocarcinidae. Smithsonian Contributions to Zoology, 432, 1 - 82. https: // doi. org / 10.5479 / si. 00810282.432", "Poupin, J. (1996) Atlas des crustaces marins profonds de Polynesie francaise. Recoltes du navire Marara, 1986 / 1996. Rapport Scientifique du Service Mixte de Surveillance Radiologique et Biologique. SMSRB, Montlhery Cedex, 59 pp.", "Cardoso, I. A. & Young, P. S. (2005) Deep-sea Oplophoridae (Crustacea Caridea) from the southwestern Brazil. Zootaxa, 1031 (1), 1 - 76. https: // doi. org / 10.11646 / zootaxa. 1031.1.1", "Pequegnat, L. H. & Wicksten, M. K. (2006) Oplophorid shrimps (Decapoda: Caridea: Oplophoridae) in the Gulf of Mexico and Caribbean Sea from the collections of the research vessels Alaminos, Oregon and Oregon II. Crustacean Reseach, 35, 92 - 107. https: // doi. org / 10.18353 / crustacea. 35.0 _ 92", "Poupin, J. (2010) Biodiversite de l'Indo-Pacifique tropical francais: 2514 especes de crustaces decapodes et stomatopodes. Rapport Scientifique de l'Institut de Recherche de l'Ecole Navale. Scientifique de l'Institut de Recherche de l'Ecole Navale, Angers / Brest, 76 pp."]}